A whole body vibration perception map and associated acceleration loads at the lower leg, hip and head. Issue 7 (July 2015) - Sonza, Anelise; Völkel, Nina; Zaro, Milton A.; Achaval, Matilde; Hennig, Ewald M.
Highlights: Whole body vibration severity perception rating was measured based on a Borg scale. Subjective perception ratings corresponded well with the acceleration magnitudes. The discomfort ratings might be related to resonance frequency of body parts. Machine settings can be chosen based on subject's sensation (Borg scale). Abstract: Whole-body vibration (WBV) training has become popular in recent years. However, WBV may be harmful to the human body. The goal of this study was to determine the acceleration magnitudes at different body segments for different frequencies of WBV. Additionally, vibration sensation ratings by subjects served to create perception vibration magnitude and discomfort maps of the human body. In the first of two experiments, 65 young adults mean (± SD) age range of 23 (± 3.0) years, participated in WBV severity perception ratings, based on a Borg scale. Measurements were performed at 12 different frequencies, two intensities (3 and 5 mm amplitudes) of rotational mode WBV. On a separate day, a second experiment ( n  = 40) included vertical accelerometry of the head, hip and lower leg with the same WBV settings. The highest lower limb vibration magnitude perception based on the Borg scale was extremely intense for the frequencies between 21 and 25 Hz; somewhat hard for the trunk region (11–25 Hz) and fairly light for the head (13–25 Hz). The highest vertical accelerations were found at a frequency of 23 Hz at the tibia, 9 Hz at the hip and 13 Hz at the head. At 5 mm amplitude, 61.5% of the subjects reported discomfort in the foot region (21–25 Hz), 46.2% for the lower back (17, 19 and 21 Hz) and 23% for the abdominal region (9–13 Hz). The range of 3–7 Hz represents the safest frequency range with magnitudes less than 1 g * sec for all studied regions.